BOLIVIAN PUBLIC FINANCES, 1882-2010. THE CHALLENGE TO MAKE SOCIAL SPENDING SUSTAINABLE*. (27th March 2014) - Peres-Cajías, José Alejandro
ABSTRACT This paper offers a long-term comparative study of Bolivian public finances using a new detailed database. First, it shows that Bolivian government revenues and expenditures were particularly small and volatile until the 1980s. Second, it stresses that, whereas the relative importance of social expenditure has grown constantly since the late 1930s, public revenues have always had an unbalanced structure. Finally, it confirms that budget deficits have been constant, at times reaching levels that were especially damaging for the overall economy. This suggests that the potential redistributive impact of Bolivian public finances was not necessarily (or not only) hindered by the lack of an explicit commitment towards redistributive expenses, but by an extreme vulnerability in the revenue side.